ANALISA KESEHATAN KEUANGAN PERUSAHAAN UNTUK MEMPREDIKSI KEBANGKRUTAN PERUSAHAAN DENGAN MENGGUNAKAN METODE ALTMAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SEKTOR KOMPONEN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011 – 2015) - Indar Khaerunnisa; Edy Cahyadi (Jurnal Ilmiah Binaniaga, 2017)
The Indonesian government has set the motor vehicle industry as one of the priority industries of the national interest, economic growth, and increased productivity. In order for the survival of a company is maintained, then the management should be able to maintain or even more spur increased performance. Various analyzes were developed to predict the beginning of the bankruptcy of the company. One analysis is widely used today is the analysis of Altman Z-Score, which this analysis refers to the financial ratios of the company. The purpose of this study was to analyze the bankruptcy of the automotive components companies that go public in Indonesia Stock Exchange year period 2011–2015. This study used a sample of four companies from the automotive components sector. Source of data is done by using secondary data. The data is processed by the method of the Z-score formula Z = 1,2X1 + 1,4X2 + 3,3X3 + 0,6X4 + 0,999X5. With the description of Z < 1,8 the company categorized into unhealthy/will be bankrupt, the value Z 1,8 < 2,99 the company is considered to be in the uncertain/grey area and the value of Z > 2,99 then the company is in a very healthy. In general, the results of these studies indicate that the four automtive components companies namely PT Astra Otoparts year 2011 value of Z = 14,67 year 2012 value of Z = 10,88 year 2013 value of Z = 13,90 year 2014 value of Z = 10,54 year 2015 value of Z = 4,94, PT Gajah Tunggal year 2011 value of Z = 5,72 year 2012 value of Z = 4,75 year 2013 value of Z = 3,10 year 2014 value of Z = 2,79 year 2015 value of Z = 1,58 and the average value of 2011-2015 periode Z = 3,59, PT Goodyear Indonesia year 2011 value of Z = 2,07 year 2012 value of Z = 2,44 year 2013 value of Z = 2,57 year 2014 value of Z = 2,02 year 2015 value of Z = 2,76, PT Indomobil Sukses Internasional year 2011 value of Z = 6,19 year 2012 value of Z = 3,99 year 2013 value of Z = 3,17 year 2014 value of Z = 2,59 year 2015 value of Z = 1,74. The average value 2011-2015 period showed 3 companies are in very healthy state and 1 company is in the uncertain/grey area. Keywords: Financial Ratio Analysis, Analysis of bankruptcy, Altman Z-Score Analysis, Automotive Components Company, Go Public.